Experimental studies on oscillation modes of vibration separation devices - Demianenko M.; Volf M.; Pavlenko I.; Liaposhchenko O. (Журнал інженерних наук)
Despite the rapid development of alternative energy sources, the role of hydrocarbons in the global fuel and energy balance remains significant. For their transportation and further processing, pre-processing is carried out using a set of equipment. In this case, the mandatory devices are separators. In terms of specific energy consumption and separation efficiency, methods based on the action of inertia forces are optimal. However, standard designs have common disadvantages. A method of dynamic separation is proposed to eliminate them. The proposed devices are automatic control systems. The object of regulation is hydraulic resistance, and elastic forces are the regulating actions. Aerohydroelastic phenomena accompany the operation of dynamic separation devices. Among them, the most interesting are flutter and buffeting. Oscillations of adjustable baffles accompany them. It is necessary to conduct a number of multifactorial experiments to determine the operating parameters of dynamic separation devices. In turn, physical experiments aim to identify patterns and features of processes occurring during vibration-inertial separation (i.e., the dependence of various parameters on velocity). Therefore, the article proposes a methodology for carrying our physical experiments on dynamic separation and a designed experimental setup for these studies. As a result, the operating modes of separation devices for different thicknesses of baffle elements were evaluated. Additionally, the dependences of the adjustable element’s deflections and oscillation amplitudes on the gas flow velocity were determined for different operating modes of vibration separation devices.